MANAJEMEN PERINTISAN JEMAAT PAULUS DALAM PELAYANAN MISI PERTAMA - Muhadi, Muhadi (Jurnal Penggerak, 2024)
In church planting, the role of correct management is very important. A healthy church is a church that has clear, orderly management and is in accordance with the vision and mission. A church leader often overlooks matters relating to management. Without realizing it, the church does not experience any relevant reforms to improve the quality of a healthy church. In this research the author uses a historical and theological analysis approach, exploring the journey of the Apostle Paul as a leader who organized and managed his first mission in spreading the Gospel in various cities in the Asia Minor region. The results of this research found that Paul used good management with several steps as a strategy in carrying out the mission. The management consists of preparation or planning with prayer and fasting, forming a mission team, dividing tasks and responsibilities, determining the mission location, contextual and wise approaches in managing problems.